ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MELAKUKAN INITIAL PUBLIC OFFERING (IPO) - Sabda Risky Juliana; Sumani Sumani (Jurnal Akuntansi, 2019)
This study aims to determine the differences in corporate financial performance before and after Initial Public Offering (IPO). Variables in this study using Current Ratio (CR), Total Assets Turn Over (TATO), Debt to Equity Ratio (DER), Return On Equity (ROE). The sample used in this study is a company that IPO in 2013-2014 as many as 37 companies with purposive sampling method. Hypothesis testing method using paired sample t-test (paired sample t-test).Based on the results of descriptive analysis shows the increase of CR means after IPO, while in TATO, DER, ROE decreased. Based on the results of paired sample T-test shows there are significant differences in CR, TATO, ROE after IPO, while DER no significant difference after IPO.